Relationship of Oxidative Stress and Some Blood Parameters with Quarters Affected by Mastitis in Dairy Cows - Akkus, T.; Dincer, P. F. Polat; Ekici, M.; Yerlikaya, Z. (Agricultural Research Communication Centre, 2023)
Background: This study was conducted to evaluate the relationship between oxidative stress and some blood parameters in different number of quarters affected with and without sub-clinical mastitis (SM).Methods: A total of 50 lactating Holstein dairy cows were used in the study. The study groups were as follows; Group 1 (negative test results and no SM), Group 2 (SM in one quarter), Group 3 (SM in two quarters), Group 4 (SM in three quarters) Group 5 (SM in four quarters). Milk samples were obtained from the infected quarters for both Somatic Cell Count (SCC) measurement and bacteriological growth/bacterial identification. Blood was collected for analysis of oxidative stress parameters (total oxidative capacity and total antioxidant capacity) and some blood parameters (glucose, total cholesterol, total bilirubin, aspartate aminotransferase [AST], alanine aminotransferase [ALT]).Result: Somatic Cell Count (SCC) was significantly lower in Group 1 than in Groups 2, 3, 4 and 5 (P<0.001). Glucose and total cholesterol levels were significantly higher in Group 5 than in Groups 1, 2, 3 and 4 (P<0.001). A significant difference was determined between all groups in respect of AST and ALT activities (P<0.001). The Total Oxidative Capacity (TOC) and oxidative stress index value (OSI) levels were significantly lower in Group 1 than in Groups 2, 3, 4 and 5 (P<0.001), while Total Antioxidant Capacity (TAC) levels were significantly higher (P<0.001). In conclusion, it was found that oxidative stress and blood-biochemistry values are significantly affected in dairy cows with sub-clinical mastitis.
Keywords: Biochemical change; Cows; Sub-clinical mastitis; Total antioxidant capacity; Total oxidant capacity